It Evaluation Based on Cobit 5 Framework at XYZ Embassy - Piyan Piyan; Sfenrianto Sfenrianto (Syntax Idea, 2095)
An embassy is a government organization located abroad and is tasked with carrying out diplomacy towards the accredited country where the embassy is domiciled. The XYZ Embassy is located on the African continent and has an organizational structure consisting of the Ambassador and several diplomats and local staff. As is the general condition of XYZ country in all countries, the XYZ Embassy is also experiencing problems especially related to ICT, such as the XYZ Embassy's IT infrastructure is inadequate, the quality of electronic goods is not good, limited ICT resources, poor energy resources, information systems that are not yet integrated and limited ICT procurement and maintenance budgets. The aim of this research is to evaluate ICT governance at the XYZ Embassy using the COBIT 5 framework so that a capability level assessment can be carried out and a Gap Analysis can be obtained and provide recommendations for improving ICT governance at the XYZ Embassy. Some of the benefits of conducting research include assessing the condition of needs in ICT management at the XYZ Embassy, helping to measure the capability level of ICT management, and recommendations in efforts to maximize and optimize the use of ICT using COBIT 5.